Governance Manajemen Wakaf Digital: Analisis Kritis Irrevocability Ikrar dan Fatwa DSN-MUI Terkini (2019–2025) - Anjani, Zubaidah; Hanif, Ahmad (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This study critically analyzes the governance of digital waqf management in Indonesia, focusing on the application of the irrevocability principle in digital declarations and the dynamics of DSN-MUI fatwas from 2020–2025. A systematic literature review (SLR) was conducted on 178 publications (2019–2025) related to digital waqf, governance, and Islamic social finance. After screening, 14 studies met the inclusion criteria. Findings reveal that digitalization enhances transparency and public participation, yet faces major challenges in regulatory fragmentation, inadequate digital infrastructure, and insufficient technical-legal guarantees of irrevocability. DSN-MUI Fatwas No. 131/2019 and No. 141/2023 provide primary legitimacy, but implementation is hindered by poor inter-institutional coordination. The study recommends establishing a National Digital Waqf Governance Framework incorporating blockchain technology and AI-assisted Shariah audits to ensure irrevocability and accountability. This framework is expected to transform digital waqf into a sustainable instrument for Islamic socio-economic development.